2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9014273
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Based Microservices Architecture for Internet of Things: Mobility Analysis Case Study

Abstract: In this paper, we describe how the microservices paradigm can be used to design and implement distributed edge services for Internet of Things applications. As a case study, traditionally monolithic user mobility analysis service is developed, with distributed and extendable microservices, for the standardized ETSI MEC system reference architecture. In each of the edge system three tiers, microservices implement the service logic with components for movement trace analysis, movement prediction and visualizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Thus, several database systems can be used in a microservice architecture, like Cassandra [57], InfluxDB [136,147], MySQL [55,78], MongoDB [18,29]. Moreover, the microservices are developed using different programming languages and frameworks such as, Python [55,78,79,146,136,81,139,54,140,142,121,28], Java OSGi [110,125], SpringBoot [71,146,115], Java [41,29,79,128,53,94], Golang [18,146,84], Node.JS [125,137], C++ [78,79,140], R [17], and even pure C [126].…”
Section: Conclusion Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several database systems can be used in a microservice architecture, like Cassandra [57], InfluxDB [136,147], MySQL [55,78], MongoDB [18,29]. Moreover, the microservices are developed using different programming languages and frameworks such as, Python [55,78,79,146,136,81,139,54,140,142,121,28], Java OSGi [110,125], SpringBoot [71,146,115], Java [41,29,79,128,53,94], Golang [18,146,84], Node.JS [125,137], C++ [78,79,140], R [17], and even pure C [126].…”
Section: Conclusion Validitymentioning
confidence: 99%
“…Further, the API Gateway is another example of an architectural feature employed in many solutions. As far as the approaches, the architectures may use a single [16,17], two [18,19], or even all three [13,20] tiers (Edge, Fog, Cloud) in the architecture to host and run the microservices to achieve the expected QoS [13,20]. Other authors proposed extra tiers beyond the traditional 3-tier approach.…”
mentioning
confidence: 99%
“…It brings a number of advantages in terms of flexibility and scalability. A few studies have been performed in the context of deployment of the MSA for various IoT applications based on the edge [17], [18] and mist computing [19]. Microservices are widely deployed in cloud data centers or edge cluster nodes in the last few years.…”
Section: B Monolithic Vs Microservices Vs Nanoservicesmentioning
confidence: 99%
“…Three criteria, namely round trip time, CPU time delay, and time distribution were considered to assess the system performance of containerization. In [31], the authors looked into the latency performance of multi-access edge computing platform running a containerbased user mobility analysis service and concluded that the low latency promise in the edge could be guaranteed with a containerized implementation. The authors in [32] provided a thorough performance benchmarking of stream data latency, scalability and resource utilization on a container-based edge This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: Related Workmentioning
confidence: 99%